2018
DOI: 10.1002/aenm.201703133
|View full text |Cite
|
Sign up to set email alerts
|

Natural Leaf Made Triboelectric Nanogenerator for Harvesting Environmental Mechanical Energy

Abstract: mechanical energy exists extensively in our daily life, such as vibration, wind, and waves. [3] However, most of this energy is wasted and long-neglected. For one thing, environmental mechanical energy is random in amplitude, low in frequently, widely distributed, unstable, and random. Therefore, the design of effective and environmental-friendly energy harvesters still has lots of technical and economic challenges. [4] Besides, IoT has made a great progress with the development of sensor, wireless communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
160
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(166 citation statements)
references
References 39 publications
5
160
0
1
Order By: Relevance
“…Wang and co-workers [64] achieved remarkable voltage value of ≈230 V and current (≈9.5 µA), respectively using natural leafs based bioinspired TNG under the optimization condition (Figure 19e (Figure 19g), then became constant. [160][161][162] Because of electrostatic shield effect, [163] direct scale-up processing is not appropriate for the single electrode mode natural Leaf-TNG.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 96%
See 3 more Smart Citations
“…Wang and co-workers [64] achieved remarkable voltage value of ≈230 V and current (≈9.5 µA), respectively using natural leafs based bioinspired TNG under the optimization condition (Figure 19e (Figure 19g), then became constant. [160][161][162] Because of electrostatic shield effect, [163] direct scale-up processing is not appropriate for the single electrode mode natural Leaf-TNG.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 96%
“…[64] They have used natural leaves to design effective TNG and proposed a green energy harvesting approach toward development of pollution free modern society. [64] They have used natural leaves to design effective TNG and proposed a green energy harvesting approach toward development of pollution free modern society.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19][20][21] However, there are several limitations on biomedical and biowearable applications for TENGs due to the synthetic polymers and nonbiocompatibility of the majority ongoing TENGs. Thus, the natural biomaterialsbased TENGs [22] have immensely attracted the researcher's attentions with the merits of biocompatibility, low cost, and plentiful raw materials. [23][24][25] Wang et al [24] reported a biodegradable and flexible chitosanbased TENG (chitosan was derived from chitin) and explored the feasibility of laser processing of constituent materials.…”
mentioning
confidence: 99%